An experimental and theoretical investigation of the structure of synthesized ZnO powder - Kaygili, Omer; Ercan, Ismail; Ates, Tankut; Keser, Serhat; Orek, Cahit; Gunduz, Bayram; Seckin, Turgay; Bulut, Niyazi; Bañares, Luis (Elsevier BV, 2018)
Abstract ZnO powder has been synthesized, characterized experimentally and its theoretical modeling carried out by density functional theory (DFT). The experimental and theoretical results were compared with each other and with the available data in the literature. A detailed crystal structure analysis was carried out using X-ray diffraction (XRD) data. Experimental and theoretical FTIR analysis, energy gap and density of states and electronic band structure calculations have been done for a complete characterization of the material. The surface morphology has been investigated by scanning electron microscopy (SEM) and energy dispersive X-ray (EDX) spectroscopy. It has been found that the electron excitation of ZnO can occur most probably at the Γ-Γ point, where the energy gap has the lowest value between the valance and conduction bands.
Keywords: ZnO; Density functional theory (DFT); X-ray diffraction (XRD); 3. Good health